Diagnosis and Treatment of Neonatal Diabetes Caused by ATP-Channel Mutations: Genetic Insights, Sulfonylurea Therapy, and Future Directions - Michela Trada; Chiara Novara; Martina Moretto; Edoardo Burzi; Davide Tinti; Luisa De Sanctis (Children)
Background: Neonatal diabetes (NDM) is a rare genetic disorder diagnosed in infants under six months of age, characterized by persistent hyperglycemia resulting from insufficient or absent insulin production. Unlike the more common forms of diabetes, such as type 1 diabetes (T1D) and type 2 diabetes (T2D), NDM is predominantly caused by monogenic mutations affecting ATP-sensitive potassium (K-ATP) channels in pancreatic beta cells. The most common mutations involved in NDM are found in the KCNJ11 and ABCC8 genes, which encode the Kir6.2 and SUR1 subunits of the K-ATP channel, respectively. These mutations prevent normal insulin secretion by disrupting the function of the K-ATP channel. While genetic advances have identified about 40 genes implicated in NDM, the KCNJ11 and ABCC8 mutations are most commonly seen. Methods: This review provides a comprehensive exploration of the genetic basis, clinical presentation, and treatment strategies for NDM including the role of sulfonylureas, which have revolutionized the management of this condition. Furthermore, it presents a detailed case study of an infant diagnosed with an ABCC8 mutation, illustrating the pivotal role of genetic testing in guiding clinical decisions. Conclusions: Finally, the article discusses challenges in management, such as the persistence of neurological impairments, and outlines potential directions for future research including genetic therapies and prenatal diagnosis.